Adaptive Social Protection in the Caribbean - Building Human Capital for Resilience : 360° Resilience Background Paper - Beazley, Rodolfo; Williams, Asha (World Bank, Washington, DC, 2021)
The Caribbean region is highly exposed to different types of shocks, some with devastating effects, ranging from climate change and disasters to external economic stresses and epidemics like the ongoing COVID-19 pandemic. Most Caribbean economies are small and open, and reliant on tourism and foreign investments, combined with high levels of poverty, which makes countries in the region vulnerable to such shocks. Shocks disproportionally affect the poor because they are often not only more exposed to them (e.g. due to their geographical location), but they are also more vulnerable to their effects. The sources of resilience available to the poor are more limited, and therefore they are often less equipped to anticipate, absorb, and recover from shocks. The social protection (SP), health, and education sectors play key roles in helping people to build human capital for resilience. These sectors contribute to strengthening the capacities of households and individuals, and in particular the poor, to anticipate, absorb, and recover from shocks. In this regard, ensuring business continuity for these services during shock events is crucial, alongside developing the capacity to rapidly adapt and deploy adequate support to people affected by shocks. Adaptive Social Protection (ASP) is concerned with how SP programs, services and systems can contribute to addressing covariate shocks through preventive, preparedness, and response actions: that is, adapting and using the capacity of the SP sector, typically developed for addressing idiosyncratic shocks, to enhance the resilience of households – and of the poor in particular